Determination of the Infection Dynamics of Escherichia coli O157:H7 by Bacteriophage ΦV10 - Michael F. Oats; Claudia P. Coronel-Aguilera; Bruce M. Applegate; Laszlo N. Csonka; Arun K. Bhunia; Andrew G. Gehring; George C. Paoli (Foods)
ΦV10 is an Escherichia coli O157:H7-specific bacteriophage that has been used to develop luminescent reporter assays for the detection of this important foodborne pathogen. Previous work demonstrated the specificity of ΦV10 for infection of E.coli O157:H7 through interaction with the O157 antigen. In addition, modification of the lipopolysaccharide (LPS) via O-acetylation prevents ΦV10 infection in an E. coli O157:H7 expressing a phage-encoded O-acetylase gene. Through assays for phage binding, plaque formation, and lysogeny using non-O157:H7 and O157: non-H7 strains, as well as complementation of an O157:H− strain, it is demonstrated in this study that both the somatic O157 antigen and flagellar H7 antigen are required for productive infection of E. coli O157:H7 by ΦV10. Together, the results indicate that the O157 antigen is required for phage binding and that the H7 antigen is necessary to complete the infection process.